Intravenous immunoglobulin as adjunct therapy for refractory pyoderma gangrenosum: systematic review of cases and case series. (1st February 2018) - Song, H.; Lahood, N.; Mostaghimi, A.
Summary: Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis. Treatment regimens for refractory cases are nonstandardized. Intravenous immunoglobulin (IVIG) is an emerging treatment with reported success, but the efficacy of IVIG for PG is unknown. In this systematic review of cases and case series, we assessed the efficacy of IVIG for the treatment of PG, as observed at our institution and reported in the literature. A retrospective chart review at two tertiary care hospitals between 2000 and 2015, and literature searches in PubMed/MEDLINE, EMBASE and Web of Science from all years were conducted. In total, there were 49 patients, including 43 patients from 26 articles and six institutional cases. There was complete or partial response in 43 (88%) patients and complete response in 26 (53%) patients. The mean time to initial response to treatment and treatment length were 3·5 (SD 3·3) weeks and 5·9 (SD 7·8) months, respectively. On average, 2·6 treatments had been trialled before IVIG initiation. IVIG was administered with systemic steroids in 43 (88%) cases. Mild adverse events, especially nausea and headache, were reported in 12 (24·5%) patients. Our systematic review suggests a potential role for IVIG as adjuvant therapy for refractory PG. Prospective clinical trials testing the efficacy of IVIG for refractory PG are needed to validate these findings.